Effect of Ageing on Acoustic Characteristics of Voice Pitch and Formants in Czech Vowels - Tykalova, Tereza; Skrabal, Dominik; Boril, Tomas; Cmejla, Roman; Volin, Jan; Rusz, Jan (Journal of voice, 2021)
BACKGROUND: The relevance of formant-based measures has been noted across a spectrum of medical, technical, and linguistic applications. Therefore, the primary aim of the study was to evaluate the effect of ageing on vowel articulation, as the previous research revealed contradictory findings. The secondary aim was to provide normative acoustic data for all Czech monophthongs. METHODS: The database consisted of 100 healthy speakers (50 men and 50 women) aged between 20 and 90. Acoustic characteristics, including vowel duration, vowel space area (VSA), fundamental frequency (fo), and the first to fourth formant frequencies (F1-F4) of 10 Czech vowels were extracted from a reading passage. In addition, the articulation rate was calculated from the entire duration of the reading passage. RESULTS: Age-related changes in pitch were sex-dependent, while age-related alterations in F2/a/, F2/u/, VSA, and vowel duration seemed to be sex-independent. In particular, we observed a clear lowering of fo with age for women, but no change for men. With regard to formants, we found lowering of F2/a/ and F2/u/ with increased age, but no statistically significant changes in F1, F3, or F4 frequencies with advanced age. Although the alterations in F1 and F2 frequencies were rather small, they appeared to be in a direction against vowel centralization, resulting in a significantly greater VSA in the older population. The greater VSA was found to be related partly to longer vowel duration. CONCLUSIONS: Alterations in vowel formant frequencies across several decades of adult life appear to be small or in a direction against vowel centralization, thus indicating the good preservation of articulatory precision in older speakers.
Keywords: akustika; akustika řeči; Humans; Acoustics; lidé středního věku; Speech Acoustics; jazyk (prostředek komunikace); fonetika; Female; Aged; mladý dospělý; dospělí; Phonetics; stárnutí; senioři; lidé; Aging; Language; Adult; ženské pohlaví; Male; Middle Aged; Czech Republic; Aged, 80 and over; Young Adult; senioři nad 80 let; Česká republika; mužské pohlaví